2024
DOI: 10.1037/sah0000447
|View full text |Cite
|
Sign up to set email alerts
|

Stories against stigma: Comparing efficacy of a perspective-taking intervention to reduce prejudice toward persons with mental illness versus persons with HIV.

Abstract: The most effective way to reduce mental illness stigma is through contact (Corrigan et al., 2012); however, such programs are difficult to implement. Researchers have turned to indirect contact with some success (Mann & Himelein, 2008), yet the exact mechanism behind narrative-based programs remains unknown. The present study seeks to isolate one possible mechanism—perspective-taking. Perspective-taking enjoys wide support in prejudice research (Batson, Early et al., 1997) but is relatively untested with menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…and behavioral intentions toward the Venezuelan immigrants. Whereas previous research in psychological laboratories has generally found support for the positive effects of perspective taking on attitudes toward outgroups (e.g., M. E. Levin et al, 2016;Mann et al, 2023;Simonovits et al, 2018;Todd & Galinsky, 2014;Vezzali et al, 2015, but see Lai et al, 2014, for an exception), our findings seem to mirror previous results where perspective taking was examined in real-life conflict situations (such as between Israel and Palestine; Bruneau & Saxe, 2012). While participants were explicitly instructed to take the perspective of refugees, such instructions apparently cannot be employed as a "quick fix" to promote more positive outgroup attitudes, not even to temporarily reduce prejudiced responses.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…and behavioral intentions toward the Venezuelan immigrants. Whereas previous research in psychological laboratories has generally found support for the positive effects of perspective taking on attitudes toward outgroups (e.g., M. E. Levin et al, 2016;Mann et al, 2023;Simonovits et al, 2018;Todd & Galinsky, 2014;Vezzali et al, 2015, but see Lai et al, 2014, for an exception), our findings seem to mirror previous results where perspective taking was examined in real-life conflict situations (such as between Israel and Palestine; Bruneau & Saxe, 2012). While participants were explicitly instructed to take the perspective of refugees, such instructions apparently cannot be employed as a "quick fix" to promote more positive outgroup attitudes, not even to temporarily reduce prejudiced responses.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, perspective taking has been shown to improve explicit and implicit evaluations as well as behavioral intentions toward outgroup members (e.g., M. E. Levin et al, 2016;Vezzali et al, 2015; for a review, see Todd & Galinsky, 2014; for an exception, see Lai et al, 2014). For instance, Mann et al (2023) found that, compared to being instructed to stay objective or given no instructions, being instructed to focus on the speaker's perspective while listening to a student with bipolar disorder or HIV speaking about the difficulties of living with their illness reduced prejudice and stigma toward the target person and group. Moreover, Simonovits et al (2018) demonstrated that compared to playing an unrelated online game, playing a roleplaying game from the perspective of an adolescent Roma who tries to start a new life in Budapest reduced anti-Roma sentiment and antipathy toward refugees.…”
Section: Perspective Taking and Prejudice: From The Laboratory To Rea...mentioning
confidence: 99%
See 2 more Smart Citations
“…Empathic concern is an otheroriented emotion that includes a positive worry over another person, whereas perspective-taking comprises the adoption of other people's point of view and seeing things from their perspectives (11). Empathic concern and perspective-taking could mitigate stigmatization because they foster understanding, combat stereotypes, promote social inclusion, reduce discrimination, and build empathic communities (12)(13)(14) [even though empathy has also a downside (15) and has been connected to selfishness (16) and the manipulation and deception of others (17)]. By empathizing with individuals who face stigmatization, people can challenge prejudice, advocate for equality, and create environments where everyone is treated with dignity and respect.…”
Section: Introductionmentioning
confidence: 99%